The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s11111-021-00390-w
|View full text |Cite
|
Sign up to set email alerts
|

Altitude and early child growth in 47 countries

Abstract: The relationship between altitude of residence and child linear growth is studied using data for 630,499 children below age 5 years born between 1992 and 2016, as recorded in 47 countries at elevations ranging from − 377 to 4498 m above sea level. Regressions are used to measure the role of household, community, and environmental factors in explaining an observed altitude effect on linear growth. Controlling for birth year and country effects, and a range of factors correlated with altitude and associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
1
2
0
Order By: Relevance
“…11 It is crucial to emphasise that altitude is only one of several factors that contribute to stunting, and its influence varies depending on other contextual factors such as economic status, healthcare facilities, and dietary choices. 33 To alleviate stunting in high-altitude locations, a comprehensive approach is required, which includes increasing access to healthcare, nutrition, sanitation, and education, as well as addressing the underlying socioeconomic determinants of health, 34 this study also confirm the findings shown in the different studies. Finally, encourage collaboration among government agencies, healthcare providers, non-governmental organisations, and community-based organisations in order to execute comprehensive and multi-sectoral stunting elimination strategies.…”
Section: Discussionsupporting
confidence: 77%
“…11 It is crucial to emphasise that altitude is only one of several factors that contribute to stunting, and its influence varies depending on other contextual factors such as economic status, healthcare facilities, and dietary choices. 33 To alleviate stunting in high-altitude locations, a comprehensive approach is required, which includes increasing access to healthcare, nutrition, sanitation, and education, as well as addressing the underlying socioeconomic determinants of health, 34 this study also confirm the findings shown in the different studies. Finally, encourage collaboration among government agencies, healthcare providers, non-governmental organisations, and community-based organisations in order to execute comprehensive and multi-sectoral stunting elimination strategies.…”
Section: Discussionsupporting
confidence: 77%
“…Children who live above 2000 masl. are shorter and lighter than their lowland counterparts (Baye & Hirvonen, 2020; Haas et al, 1982; Shively & Schmiess, 2021; Toselli et al, 2001), this configures a particular somatotype with a dominant mesomorphy and ectomorphy (Goon et al, 2013; Malik et al, 1986; Mateu, Valladares & Castillo, 2018; Pandey & Malik, 1990; Singh et al, 2007; Toselli et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia is a drop in the normal level of tissue oxygen tension, and it is well-known that children permanently exposed to hypoxia at altitudes greater than 3,000 m above sea level (hereinafter referred to as "m") exhibit phenotypical adaptation and different growth patterns (1). Existing global and local data suggest that at 2,000 m, the adverse effect of altitude on child height growth would intensify (2), and Tibetan children residing above 3,500 m had a two-to-sixfold increased risk of stunting compared to those residing at 3,000 m (3). The adaptation of blood pressure regulation at high altitude is another consequence of hypoxia with major epidemiological significance.…”
Section: Introductionmentioning
confidence: 99%